Changes in the microbial population during storage of the smoked fish, Amhlypharyngodon mola of Manipur - Lilabati, H; Viswanath, W (Indian Journal of Fisheries, 2011)
Changes in the total plate counts of bacteria (TPC), fungi (TFC), coliform and pathogenic bacteria viz, Escherichia coli, Salmonella, Staphylococcus aureus and faecal Streptococci, and the fungal flora during storage of smokeA Amhlypharyngodon mola were studied. There was a strong relationship between the microbial counts and meteorological data during the storage. In the samples of monsoon, summer and winter, fungal colonies were visible respectively on the 75th, 90th and 105th day. TFC was highest in monsoon season. In all the seasons, coliform, Staphylococcus aureus and faecal Streptococci were detected in the beginning of the storage, which gradually reduced and vanished. The seasons in which coliforms appeared for the longest duration was summer (15 days). Staphylococcus aureus, monsoon (45 days), faecal Streptococci, winter (60 days.) E. coli. and Salmonella were not detected in all the seasons. Aspergillus niger, Penicillium funiculosum, Trichoderma longibranchiatum and Aspergillus flavipes were dominant in monsoon; A. niger, Penicillium funiculosum and Cladosporium cladosporoids in winter and A. niger, A. repens and A. flavipes in summer. Of all the seasons, storage life was shortest in monsoon.